HUBUNGAN ANTARA STATUS IMUNISASI BCG DENGAN KEJADIAN TUBERKULOSIS PARU PADA ANAL BALITA USIA < 5 TAHUN DI BALAI KESEHATAN PARU MASYARAKAT (BPKM) PURWOKERTO - Rahmaya Nova Handayani; Noor Yunida Triana; Gatri Asti Putri (Universitas Harapan Bangsa Purwokerto, 2013)
Pulmonary tuberculosis in children remains a public health problem in Indonesia. LungHealth in the Community hall (BKPM) Purwokerto obtained prevalence of pulmonarytuberculosis in children in the past 6 months was as high as 30 children under five and two of 30children under five have never immunized BCG. The method used to approach a case-control study, subjects were 30 person group that is thecase of children who have tuberculosis and 30 control group who did not tuberculosis.Univariate analysis used percentage analysis, bivariate analysis used Chi Square (X Â²) and OddsRatio (OR). The results showed that most respondents had at BCG immunization (93.3%). BCG immunizationstatus with the incidence of pulmonary tuberculosis revealed no statistically significantrelationship where p = 0.500 (p> 0.05). The conclusion from this study of children under five are yaitu sebagian at BCGimmunization, it can be concluded also that there was no association between BCG immunizationstatus with the incidence of pulmonary tuberculosis in children under five age â‰¤ 5 years in theLung Center of Public Health (BKPM) Purwokerto. Key words: BCG immunization status, pulmonary tuberculosis, child